2021
DOI: 10.2147/tcrm.s251668
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alpelisib in the Treatment of PIK3CA-Mutated Breast Cancer: Patient Selection and Clinical Perspectives

Abstract: The PI3K/AKT/mTOR pathway has long been known to play a major role in the growth and survival of cancer cells. Breast tumors often harbor PIK3CA gene alterations, which therefore constitute a rational drug target. However, it has taken many years to demonstrate clinically-relevant efficacy of PI3K inhibition and eventually attain regulatory approvals. As data on PI3K inhibitors continue to mature, this review updates and summarizes the current state of the science, including the prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 95 publications
(144 reference statements)
2
42
1
Order By: Relevance
“…PIK3CA encodes the catalytic subunit of PI3K performing phosphorylation, triggering the downstream signaling of cell growth/proliferation and cell survival inter alia, facilitating uncontrolled cell growth when the genome is harboring pathogenic PIK3CA mutations [29]. The biological drug, Alpelisib, is specifically inhibiting PI3K-signaling in the PI3K/AKT signaling pathway [30]. The phosphatase PTEN is contributing the regulation of PI3K phosphorylation, hence controlling PI3K/AKT downstream signaling [31,32].…”
Section: Pten and Tp53 Amplicon Observationmentioning
confidence: 99%
“…PIK3CA encodes the catalytic subunit of PI3K performing phosphorylation, triggering the downstream signaling of cell growth/proliferation and cell survival inter alia, facilitating uncontrolled cell growth when the genome is harboring pathogenic PIK3CA mutations [29]. The biological drug, Alpelisib, is specifically inhibiting PI3K-signaling in the PI3K/AKT signaling pathway [30]. The phosphatase PTEN is contributing the regulation of PI3K phosphorylation, hence controlling PI3K/AKT downstream signaling [31,32].…”
Section: Pten and Tp53 Amplicon Observationmentioning
confidence: 99%
“…Thus, drugs against different-level PI3K networks have been evaluated in clinical trials ( Engelman, 2009 ; Thorpe et al, 2015 ). Alpelisib (BYL719, Figure 1A ), an oral selective, small-molecule, and α-specific class I PI3K inhibitor, can selectively inhibit wild-type and mutant p110α approximately 50 times more effective than other subtypes ( Brana and Siu, 2012 ; Furet et al, 2013 ; Chang et al, 2021 ). Several studies have demonstrated the efficacy of treating breast cancer as a single agent and combination therapy ( Miller et al, 2010 ; Juric et al, 2018 ; Juric et al, 2019 ; Sharma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These drugs were selected as they are most widely used in clinical practice [ 32 ]. Similarly, BYL719 was selected as the PI3K inhibitor as it is widely used for the treatment of PI3K-mutated tumours [ 33 ].…”
Section: Discussionmentioning
confidence: 99%